(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
The characteristics of film flow field have important effects on the quality of hydrodynamic polishing. Oriented preparation requirements of amorphous film substrate, in order to further study the floating height of hydrodynamic polishing base plate in working conditions, the mathematical model is established and the theoretical analysis has been carried out for the wedge hydrodynamic floating polishing base plate. The relationship between buoyancy and floating height is researched. The floating height is calculated under the known loads, and then the pressure distribution along the circumferential direction of base plate is analyzed. Film flow field is simulated and analyzed using the FLUENT based on the calculated floating height. It indicts that the bearing capacity of wedge combination plane decreases with the increase of floating height, and the downward trend slows down gradually. The pressure peak distributes near the interface of wedge flow field and parallel flow field. Through the pressure distribution comparison of simulation and calculation, the correctness of the mathematical model and simulation method is verified.